2010
DOI: 10.5251/abjna.2010.1.3.321.325
|View full text |Cite
|
Sign up to set email alerts
|

Performance and economics of production of broiler chickens fed sorghum or millet as replacement for maize in the semi-arid zone of Nigeria

Abstract: The effects of replacing maize with sorghum or millet on the performance and economics of production of broiler chickens were investigated in a 42 -day feeding trial. One hundred and eighty (180) (Anak-2000) broiler chicks weighing averagely 351.7±5.7g were randomly allotted to four experimental diets in which maize (T 1 ) control, pearl millet (T 2 ), low tannin sorghum (T 3 ) and high tannin sorghum (T 4 ) served as the energy sources in a randomized block design (RBD). Each treatment consisted of 45 birds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
12
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
9
12
1
3
Order By: Relevance
“…The energy and protein content of sorghum used in the present study is 3986.4 Kcal/kg DM and 11.4%, respectively which is comparable with that reported by [7] 11.6% CP and 3800.1 Kcal/kg DM ME. Douglas et al [14] reported ME of 3838 and 3200 kcal/kg for low and high-tannin sorghum, respectively.…”
Section: Results Of Chemical Analysissupporting
confidence: 78%
See 4 more Smart Citations
“…The energy and protein content of sorghum used in the present study is 3986.4 Kcal/kg DM and 11.4%, respectively which is comparable with that reported by [7] 11.6% CP and 3800.1 Kcal/kg DM ME. Douglas et al [14] reported ME of 3838 and 3200 kcal/kg for low and high-tannin sorghum, respectively.…”
Section: Results Of Chemical Analysissupporting
confidence: 78%
“…Similar to the starter phase the total and daily DMI during finisher were not significantly (P>0.05). The present results agrees with results of Medegu et al [7] who reported no significant difference in DMI intake in chick fed sorghum or millet as replacement for maize in semi-arid zone of Nigeria. Cramer et al [20] also reported similar DMI were recorded in chicks fed Sorghum-based diets subjected to various manufacturing procedures from 3-6 weeks.…”
Section: Dry Matter Intakesupporting
confidence: 83%
See 3 more Smart Citations